Short-term effects of analysts recommendations in Spanish blue chips returns and trading volumes - García, Josep (Estudios de Economía, 2016)
The purpose of this paper is to investigate the effects of stock recommendationsin returns and trading volumes. Unlike previous research we have investigatedthe five most usual types of recommendations: buy, outperform, hold, underperformand sell. The methodology we propose is also different from previousstudies. From our results we conclude that positive (negative) abnormal returnsare associated to positive (negative and neutral) recommendations, the day ofpublication of the recommendation and the day before, but not the day afterpublication. We also document an asymmetry in the effect of recommendationon the stock trading volume, following the sign of the recommendation.